Accounting for Research: Academic Responses to Research Performance Demands in an Australian University. Issue 3 (11th November 2016) - Martin‐Sardesai, Ann; Irvine, Helen; Tooley, Stuart; Guthrie, James
Abstract : This study examines the perceptions of individual academics about performance management systems (PMS) developed by an Australian university to meet government research assessment requirements. Using a case study method, the research examines the period 2006–2010 within a university, relying on academics' responses to a survey on the effect of research PMS, contextualised with publicly available organisational documents. The case study university performed well in the Australian Government's first research assessment exercise, Excellence in Research for Australia (ERA) 2010. However, academics reported increasing levels of stress and decreasing job satisfaction, consistent with research that identifies the commodification of academic research. This process of commodification has occurred as a result of the implementation of PMS designed to assess academics' research‐focused performance and thereby strengthen the university's performance under ERA. In investigating in detail the responses of individual academics to Australia's research assessment initiative, the paper reveals a disconnect between the macro‐institutional demands placed on the higher education sector, university changes made to accommodate these demands, and the ability of academics to meet these demands in a sustainable way. Abstract : The paper examines the perceptions of individual academics about performance management systems developed by an Australian university from 2006‐2010 to meet government research assessment requirements. The case study university performed well in the Australian Government's first research assessment exercise, Excellence in Research for Australia 2010. However, academics reported increasing levels of stress and decreasing job satisfaction, consistent with research that identifies the commodification of academic research.